Rancang Bangun Sistem Informasi Berbasis Website pada Kantor Wali Nagari Simalidu - Apriliya, Lola; Yusran, Yusran; Susanti, Evi Yulia (Jurnal Ilmiah Sistem Informasi, 2025)
The Wali Nagari Office of Simalidu continues to face challenges in disseminating information due to the lack of an official digital platform. Information is currently delivered manually via bulletin boards, limiting public access and reducing efficiency. This study aims to design and develop a website-based information system for the Wali Nagari Office of Simalidu to improve communication effectiveness between the local government and the community. The research applies the Waterfall method, starting from requirements analysis, system design, implementation, and system testing. The system was developed using the PHP programming language and MySQL database. The main features include a homepage, a village profile, news/information, activities, employee data, a message page, and a contact page. System testing was conducted using the Blackbox Testing method to ensure that all functions operate as expected. The results show that the website-based information system enables village officials to deliver information quickly, accurately, and effectively to the public. It also allows the community to easily access up-to-date information regarding activities, profiles, and services at the Wali Nagari Office of Simalidu. Thus, this system improves transparency, accountability, and the quality of public services.